Intervensi Berbasis Minfulness untuk Mengurangi Stres pada Mahasiswa - Tania Alifiara Arijanto; Yahya Muhidin; M. Fahmi Aufar Asyraf; Endang Wahyuni; Rifandy Alif Agrianto (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
College students as young adults have several expectations and burden from the society, including they who majored psychology with tough workloads and expectations. Current research aim to determine the impact of MBSR-based intervention to reduce stress levels in College students. The research method used was an one group pretest-posttest experimental research design with 40 Psychology of X student as participants using purposive sampling techniques and PSS-10 data collection techniques. The intervention used was mindfulness-based training to reduce stress (MBSR) with 2-weeks intervention program. The analysis techniques used were paired t-test (sig 0.000 < 0.05) and cross-tabulation (men = 6.73; women = 9.81). The results shows that there was a significant effect of MBSR-based training on reducing stress in College students; which female students have a greater level of stress reduction than men students. This research proves that mindfulness-based training is able to reduce stress in college students.